The rise of transcutaneous drug delivery for the management of alopecia: a review of existing literature and an eye towards the future. (4th July 2019) - Wipf, Angela; Boysen, Nicholas; Hordinsky, Maria K.; Dando, Emily E.; Sadick, Neil; Farah, Ronda S.
ABSTRACT: Introduction : Fractional lasers and microneedling devices are increasingly used with topical drugs to treat various conditions, including alopecia, as they grant access to dermal structures such as hair follicles and cutaneous vasculature. Objective : To perform a comprehensive review on transcutaneous drug delivery for the management of alopecia. Methods : PubMed, Embase, and Ovid Medline databases were searched using terms including: alopecia, microneedling, lasers, androgenetic alopecia (AGA), alopecia areata (AA), drug delivery. Articles were examined for inclusion criteria: diagnosis of alopecia regardless of type, use of fractional laser or microneedling devices, and subsequent administration of topical medication. Results : 8 studies, 6 prospective clinical trials and 2 case series, examining either AA or AGA were identified. For AA, five studies examined microneedling together with topical triamcinolone in three of these, while two studies used photodynamic therapy. Regarding AGA, two studies used topical minoxidil plus microneedling, and one examined topical finasteride with fractional erbium glass laser. Improvement was seen in 6 of the 8 studies. Discussion : Transcutaneous drug delivery via fractional laser and microneedling is a promising modality with preliminary evidence for increased hair regrowth over topical therapy alone. Further studies are needed to elucidate treatment parameters and appropriate device selection for drug delivery.